Cutaneous phaeohyphomycosis caused by Exophiala dermatitidis in an immunosuppressed patient: A case report and brief review - Jéssica L. Bueno; Iago G. Ferreira; Cecília B. Severo; Laura Luzzato; Melissa O. Xavier; Rodrig Vettorato (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Phaeohyphomycosis is a group of fungal infections caused by filamentous dematiaceous fungi, which have melanin in their cell walls. Phaeohyphomycosis has four clinical forms: superficial, subcutaneous, systemic, and disseminated. Although rare, the subcutaneous form shows a significant prevalence in immunocompromised individuals, especially in solid organ transplant recipients. We report a case of subcutaneous phaeohyphomycosis in a renal transplant patient, caused by the species Exophiala dermatitidis. Although the case reveals characteristic clinical manifestations of the disease, laboratory and cultural findings were atypical. Based on this case of subcutaneous phaeohyphomycosis, a brief literature review is carried out on this rare and important fungal infection in medical practice.